An Edge Container Migration Optimization Method for Multi-service Intelligent Resource Scheduling of Distribution Networks - Shuai LI; Di XU; Xiangyu WEN; Jiaxin ZHANG (Zhongguo dianli)
Edge container migration technology can achieve intelligent scheduling of service data from resource-constrained servers to resource-sufficient servers. Based on the container migration technology, the container migration capacity, delay gain model and the weighted delay gain maximization problem are formulated for the distribution network multi-service resource scheduling scenarios. An edge container dynamic matching migration optimization method is proposed, which can realize the perception of the service priority, migration capacity, and latency requirements through the adaptive adjustment of the price increment. The simulation results demonstrate that compared with traditional algorithms, the proposed method can validly improve the data processing delay performance for distribution network.